2013
DOI: 10.1371/journal.pone.0064212
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of the Cynomolgus Macaque Gut Microbiota to Shigella Infection

Abstract: Little is known about the role of gut microbiota in response to live oral vaccines against enteric pathogens. We examined the effect of immunization with an oral live-attenuated Shigella dysenteriae 1 vaccine and challenge with wild-type S. dysenteriae 1 on the fecal microbiota of cynomolgus macaques using 16 S rRNA analysis of fecal samples. Multi-dimensional cluster analysis identified different bacterial community types within macaques from geographically distinct locations. The fecal microbiota of Mauritia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Although Ruminococcus , Oscillospira , and Lactobacillus are known constituents of cynomolgus macaque flora[14], Cloacibacterium and Limnohabitans are not often observed in vertebrates. However, Cloacibacterium has been observed in the gastrointestinal tract of patients with adenomas[15], and Limnohabitans has been observed in patients with cellulitis[16] .…”
Section: Resultsmentioning
confidence: 99%
“…Although Ruminococcus , Oscillospira , and Lactobacillus are known constituents of cynomolgus macaque flora[14], Cloacibacterium and Limnohabitans are not often observed in vertebrates. However, Cloacibacterium has been observed in the gastrointestinal tract of patients with adenomas[15], and Limnohabitans has been observed in patients with cellulitis[16] .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that the gut microbiota could influence vaccine efficacy in human and non-human primates (Valdez et al, 2014). For instance, a study using Cynomolgus macaques supports the idea that a stable and more diverse gut microbiota correlates with a better response to vaccination and subsequent immunity (Seekatz et al, 2013). This finding is consistent with another study involving a small human cohort, in which the majority of individuals that responded to vaccination had greater community richness and diversity amongst their gut microbiota (Eloe-Fadrosh et al, 2013).…”
Section: Adjuvant Properties Of the Microbiota: Role In Infection Vamentioning
confidence: 94%
“…In a related study by the same group, Macaques of different geographic origins (with distinct genetic makeup and a different MHC allele repertoire) were immunized with two live attenuated Shigella disenteriae (S. dysenteriae) vaccine candidates [84]. Protection was evaluated by response to subsequent challenge with wild type S. dysenteriae.…”
Section: Influence Of Intestinal Microbial Diversity On Vaccine Respomentioning
confidence: 99%